Use of ultrasonic velocity travel time to estimate uniaxial compressive strength of granite and schist in Malaysia - Lai, G.T. (Penerbit Universiti Kebangsaan Malaysia, 2016)
The uniaxial compressive strength (UCS) is one of the most common mechanical parameters required in geotechnical engineering to characterize the compressive strength of rock material. Measurements of UCS are expensive, time consuming, destructive and thus, not favorable in the presence of limited samples. Therefore, a simple yet practical application is needed for the estimation of UCS. This research presents two correlations to predict UCS values for granite and schist by using ultrasonic velocity travel time (tp) from ultrasonic tests. The validity of the practical approach presented in this research is confirmed based on the strong correlations developed from the experimental tests conducted. For the entire data set, the correlation between UCS and ultrasonic velocity travel time was expressed as UCS = 217.2 e-0.016(tp) for granite and UCS = 1110.6 e-0.037(tp) for schist and the coefficient of determination (R2) value for both granite and schist is 0.93. These correlations may be useful for applications related to geotechnical engineering designs.